A 65-kb deletion survey identifies a distal cis- regulatory region for red-light induction of Ghd7 , a key rice floral repressor - Yuko Ogo; Takumi Kawauchi; Manaki Mimura; Ken Naito; Hironori Itoh; Takeshi Izawa (Proceedings of the National Academy of Sciences, 2025)
The Ghd7 ( Grain number, plant height, and heading date 7 ) gene integrates red light signals and circadian rhythms to control floral repression under long-day conditions in rice. CRISPR/Cas9 systems were employed to create a series of deletion mutant lines in the upstream regions of Ghd7 , covering a 65-kb genomic region from its transcription start site (TSS). These deletions ranged from 2 to 25 kb in size. Three deletion lines, those from 0 to −3 kb (0/−3 K), −20 to −40 kb (−20/−40 K), and −26 to −30 kb (−26/−30 K) from the TSS, resulted in early flowering, similar to Ghd7 knockout lines. The −20/−40 and −26/−30 K lines exhibited a loss of acute Ghd7 morning induction. Night-break experiments consistently supported these findings, suggesting that the key cis- regulatory region for red light responses was located within the 3.7-kb region in −26/−30 K. In seedlings of the 0/−3 K deletion line, which retains the −29 to −86 bp region, Ghd7 showed a diurnal pattern similar to wild type. This suggests that the deleted region in 0/−3 K is dispensable for both circadian rhythms and red-light responses. Further analyses of two deletion lines within the −26/−30 K region allowed us to narrow down the core cis- regulatory elements, responsive to morning-light signals, within a 228-bp segment located at 28-kb upstream of the TSS in Ghd7 .